Ekspresi Emosi dalam Tuturan Tokoh Atta Pada Film Jumbo: Kajian Psikolinguistik - Mahbety, Ezia Rahma; Salamah, Siti (Balai Bahasa Sulawesi Selatan, 2025)
This study aims to examine the expression of emotion in the speech of the character Atta in the film